De-carbonizing Hong Kong-What energy strategies are effective?. Issue 2 (November 2020) - Cheng, Vincent
Abstract: Buildings account for 67% of carbon emission and up to 90% of electricity consumption of Hong Kong. One third of our electricity is used on air-conditioning, which naturally become a key to decarbonization of the City. District Cooling System (DCS) is one of the most important sustainable infrastructures as stipulated in the Hong Kong's Climate Action Plan 2030+. As one of the key initiatives to increase the awareness of energy efficiency concept to the community, the HKSAR Government has promoted the adoption of DCS in the Kai Tak Development (KTD) and other planned New Development Areas (NDA). By applying the DCS, the cooling load could be shared amongst the diversified cooling requirements of various building types in the same district, thus the benefits including the improvement of energy efficiency, reduction of standby capacity and spatial requirements can be enjoyed. In recent years, Hong Kong has amassed many experiences on DCS. Successful implementation of DCS at KTD has provided many valuable know-hows on its design, construction and operation. Many challenges on the implementing DCS including the land matter, design, planning, environmental and regulatory arrangements have been resolved and paved the way for the wider application in other NDAs such as the Tung Chung New Town Extension (East) and Kwu Tung North. For each of these NDAs, many site-specific constraints are required to be investigated and addressed. This paper will discuss the DCS implementation issues, highlighting the lessons learnt and the possible solutions for wider adoption of DCS in Hong Kong.